The Northern Gemer (Šoškára) dialect of Romani and its phonological peculiarities - Elšík, Viktor (Romano džaniben, 2020)
The Northern Gemer dialect is a cluster of closely related local varieties of Central Romani spoken in the northeast of the Gemer region of Slovakia. The dialect stands out in having undergone a perceptively salient series of shifts in the place of articulation of sibilants, which clearly delimit the dialect against neighbouring dialect regions and, at the same time, result in a phonologically uneconomical and typologically rare system of sibilants. In addition to background information on the sociolinguistic situation and the dialectological position of the dialect, the present paper provides a detailed diachronic analysis of the phonological system of sibilants in Northern Gemer Romani, discussing both developments within the sibilant system and developments of sibilants from non-sibilant consonants. While some of the changes may be convincingly motivated by phonological convergence due to the speakers’ bilingualism in a contact language, other changes require an internal explanation and a reference to universal tendencies of sound change or to structural phonological parameters.